Acute Liver Injury due to Glecaprevir/Pibrentasvir in a Patient with Chronic Hepatitis C Virus Infection without Cirrhosis - Ayushi Jain; Khalid Mumtaz (Avicenna Journal of Medicine, 2022)
We reported a rare case of acute liver injury in a patient with chronic hepatitis C virus infection without cirrhosis 4 weeks after initiation of glecaprevir/pibrentasvir. After prompt cessation of antiviral therapy, liver enzymes rapidly improved toward baseline. This case reflects the need to remain vigilant for the development of acute liver injury after initiation of glecaprevir/pibrentasvir even without a diagnosis of cirrhosis.